Effect of methonolic extract of Vitex negundo on haloperidol induced catalepsy in albino mice - Kamlekar, Sandeep Kumar; Gupta, Sangita (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Plants are being used in traditional medicine since history of mankind. The knowledge of these medicinal plants has accrued in the course of many centuries leading to medicinal systems in India such as Ayurveda, Unani and Siddha. Objective: In the present study, we evaluated the anticataleptic efficacy of Vitex negundo, a polyherbal formulation in haloperidol induced catalepsy in mice. Methods: Five groups (n=6) of male albino mice were used in the study. Catalepsy was induced by i.p. administration of haloperidol (1 mg/kg). The degree of catalepsy (cataleptic score) was measured as the time the animal maintained an imposed posture. We compared the anticataleptic efficacy of Vitex negundo (50, 100, 200 mg/kg) with standard received Pheniramine maleate 10 mg/kg, i.p. Results: In vehicle treated animals, haloperidol (1 mg/kg. i.p.) produced the maximum catalepsy at 180 min (46.78±3.78 min). Standard treated as Pheniramine maleate 10 mg/kg, i.p. shows maximum at 120 min. 19.24±1.32. Test herb, i.p. Methanolic extract of Vitex negundo (50, 100, 200 mg/kg, i.p.) significantly potentiated haloperidol induced catalepsy at each time interval, in a dose dependent manner. At dose 50, 100 and 200mg/kg, extract of Vitex negundo (Linn.) roots showed maximum cataleptic score 12.34±0.78, 14.43±0.43 and 15.43±0.67 min, respectively at 120 minutes in haloperidol treated animals. Conclusions: The present study indicates that the methanolic extract of Vitex negundo reduces haloperidol-induced catalepsy in mice.